SEMIOTIKA IKLAN AUDIOVISUAL SUNTORY ALL FREE - Putri, Ayu Novitasari (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This thesis entitled “Semiotic Analysis of Suntory All Free Audiovisual Advertising”This study focuses on the verbal-visual signs audiovisual advertisement. The study is aimed at describing the sign and meaning of verbal and visual signs throught the signifier and signified concept of semiotics in Japanese audiovisual advertising. This research combined qualitative and quantitative method to analize the data. The data in this study is from Suntory All Free audiovisual advertising. Those data were analyzed based on theory of Gillian Dyer about verbal and visual aspect, theory about semiotics (relation of signifier and signifie) proposed by Roland Barthes. The result of the analysis shows that there are seven verbal signs and twelve visual signs in Suntory All Free audiovisual advertising Moteki no Papa edition and there are six verbal signs and fourteen visual signs in Suntory All Free audiovisual advertising Musume no Teryori edition. The messages obtained from the meaning of verbal and visual signs of Suntory All Free audiovisual advertising are Suntory All Free beer has a composition that’s good for health because it contains no alcohol, carbohydrates, and calories, free consumed at any season, can be drunk by anyone, free enjoyed anytime, doest’t couse drunk, doest’t couse obesity, can be drunk with any food, and more enjoyable consumed by pouring into a glass. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: audiovisual advertising, verbal signs, visual signs, semiotic